Fate of heavy metals in Colorado waters and rivers - Brennan, E. W., author; Lindsay, Willard Lyman, 1926-, author; Colorado Water Resources Research Institute, publisher (Colorado State University. Libraries, 1992)
Reclamation of contaminated wetlands polluted by acid mine drainage will require a greater understanding of the interaction between contaminated waters and sediments. In high altitude meadows, continual flooding can maintain an anaerobic condition. Oxidized sediments showed an increase in zinc (Zn) and sulfur (S) concentration, compared to sediment-solution at initially taken from the site. The addition of acid mine water to sediments in a reducing environment had a significant effect on Zn concentrations. The additions of electrons from organic substrates lowered the concentration of Zn by approximately 10 fold. As expected, the deduction process also lowered redox and decreased total sulfur in solution. Zn sulfide precipitation was verified with the chemical speciation program, MINTEQA2.
December 15, 1992.
Keywords: Water quality -- Colorado; Heavy metals -- Environmental aspects; Acid mine drainage -- Environmental aspects; Wetland ecology -- Colorado